N,N′-Bis(pyridin-3-ylmethyl)ethanediamide monohydrate: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Tiekink, Edward R. T. * (International Union of Crystallography, 2020)
The molecular structure of the title bis-pyridyl substituted diamide hydrate,C14H14N4O2H2O, features a central C2N2O2 residue (r.m.s. deviation = 0.0205 A˚ ) linked at each end to 3-pyridyl rings through methylene groups. The pyridyl rings lie to the same side of the plane, i.e. have a syn-periplanar relationship, and form dihedral angles of 59.71 (6) and 68.42 (6) with the central plane. An almost orthogonal relationship between the pyridyl rings is indicated by the dihedral angle between them [87.86 (5)]. Owing to an anti disposition between the carbonyl-O atoms in the core, two intramolecular amide-N—HO(carbonyl) hydrogen bonds are formed, each closing an S(5) loop. Supramolecular tapes are formed in the crystal via amide-N—HO(carbonyl) hydrogen bonds and ten-membered {HNC2O}2 synthons. Two symmetry-related tapes are linked by a helical chain of hydrogen-bonded water molecules via water-O—HN(pyridyl) hydrogen bonds. The resulting aggregate is parallel to the b-axis direction. Links between these, via methyleneC—HO(water) and methylene-C—H(pyridyl) interactions, give rise to a layer parallel to (101); the layers stack without directional interactions between them. The analysis of the Hirshfeld surfaces point to the importance of the specified hydrogen-bonding interactions, and to the significant influence of the water molecule of crystallization upon the molecular packing. The analysis also indicates the contribution of methylene-C—HO(carbonyl) and pyridyl-C—HC(carbonyl) contacts to the stability of the inter-layer region. The calculated interaction energies are consistent with importance of significant electrostatic attractions in the crystal.